Knowledge sharing behaviour and its predictors in United Arab Emirates Universities - Skaik, Huda Alami; Othman, Roslina (Penerbit UTM Press, 2014)
The main objectives of this research are to (i) explore the relationship between types of knowledge and academics’ knowledge sharing behaviour, (ii) examine the relationship between knowledge sharing behaviour and its predictors based on the Theory of Planned Behaviour, and (iii) examine the motivating and hindering factors that may influence academics’ knowledge sharing behaviour. Adopting Ajzen’s Amended Theory of Planned Behaviour, this research used the quantitative research approach employing an online survey using a questionnaire to collect data from academics in ten public universities in United Arab Emirates. Data were analyzed using SPSS and PLS-SEM. The analysis process involved (i) assessment of the measurement model to evaluate the items reliability and validity, (ii) assessment of the structural model to evaluate its validity, path coefficients, and test the hypotheses, as well as (iii) assessment of the mediating relationships. The results revealed that academics’ knowledge sharing behaviour is significantly influenced by explicit knowledge, tacit knowledge, and intention to share knowledge. The results also showed that intention itself is significantly influenced by attitude, subjective norms, self-efficacy, but not influenced by controllability. Moreover, attitude is significantly and positively influenced by trust and reputation as motivators of knowledge sharing behaviour. Whereas, controllability is significantly and negatively influenced by lack of time and poor communication as barriers of knowledge sharing behaviour.